2020
DOI: 10.1136/bmjopen-2019-034304
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of treatment interventions for patellar tendinopathy: a protocol for a randomised controlled trial

Abstract: IntroductionPatellar tendinopathy is a degenerative disease of the patellar tendon, which affects athletes from a variety of sports, and is especially predominant in sports involving high-impact jumping. The aim of this study is to determine the additional effect of two interventions combined with eccentric exercise and compare which one is the most effective at short-term and long-term follow-up for patients with patellar tendinopathy.Methods and analysisThis study is a randomised controlled trial with blinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, it is necessary to develop RCTs analyzing not only the effect but also comparing the effectiveness between different MIT such as DN and PNE. Fortunately, this review found two high quality protocols published that aim to compare the effects of PNE and DN in PT [ 41 ] and plantar heel pain [ 48 ], although results are not available yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is necessary to develop RCTs analyzing not only the effect but also comparing the effectiveness between different MIT such as DN and PNE. Fortunately, this review found two high quality protocols published that aim to compare the effects of PNE and DN in PT [ 41 ] and plantar heel pain [ 48 ], although results are not available yet.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, MIT that do not infiltrate any substances such as DN or PNE showed a high increase of studies in the last years, although the studies published are still of low quality except for the one published by Dragoo et al [ 21 ]. However, there was a protocol published by Lopez-Royo et al [ 41 ] analyzing the additional effects of both DN and PNE over EE whose results have not published yet, but that will increase the knowledge in this field. On the other hand, other therapies including the infiltration of substances, such as PRP therapy, were associated with a significant improvement in functionality and pain at posttreatment [ 21 , 34 37 ] and at follow-up measurements [ 21 , 35 37 ] and a significant decrease in hypoechogenicity and tear size at 6 months [ 37 ] in patients with PT, with no significant differences between one or two PRP injections.…”
Section: Reviewmentioning
confidence: 99%
“…Progressive loading from isometric to eccentric strength work without exacerbating the patients pain has been shown to be more successful in the treatment and management of patella tendinopathy, without the addition of other manual therapy techniques 2,4,21,26 . This was successfully demonstrated within the present case study.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that this added supplementation facilitates tissue repair by increasing amino acid levels within the blood, with no side effects noted 28,29 . In addition to this to modulate pain and enhance function, glyceryl trinitrate (GTN) patches were utilised 4,30,31 . GTN patches consistently used within the patient's tolerance levels with a structured rehabilitation programme have exhibited very good patient outcomes within tendinopathy cases 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation